2021
DOI: 10.21203/rs.3.rs-636186/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One year of cyclic unrest in a hydrothermal field as a harbinger of a volcanic eruption

Abstract: One year of deformation and seismicity prior to a volcanic eruption in March 2021 at an oblique plate boundary in Iceland created a unique opportunity to study the interaction between upwelling magma and geothermal processes. We apply poroelastic modelling to explain satellite geodetic data showing three uplift and subsidence cycles at the Svartsengi geothermal field and use gravity data to constrain the density of intruded material. We use recordings on optical cable to generate a high-resolution earthquake c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, before 2021 it had not erupted in more than 6000 years (Saemunds-son and Sigurgeirsson, 2013) and hence does not follow this episodic pattern of volcanism on the Peninsula. The 2021 eruption at Fagradalsfjall may be signalling the onset of a new eruption period on the Reykjanes Peninsula (Çubuk-Sabuncu et al, 2021;Flóvenz et al, 2022;Geirsson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, before 2021 it had not erupted in more than 6000 years (Saemunds-son and Sigurgeirsson, 2013) and hence does not follow this episodic pattern of volcanism on the Peninsula. The 2021 eruption at Fagradalsfjall may be signalling the onset of a new eruption period on the Reykjanes Peninsula (Çubuk-Sabuncu et al, 2021;Flóvenz et al, 2022;Geirsson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Depths range between several meters and 10 km. Events are particularly shallow beneath the geothermal field where the brittle‐ductile boundary domes up and deeper further away from it (Flovenz et al., 2022). We find no evidence of an initial occurrence of earthquakes further in the east followed by a subsequent westward progression over time, however, we cannot rule out that seismicity affects our measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency for velocity changes to be measured first in the east and then in the west is generally consistent with our observations. Flovenz et al (2022) propose a model for the observed deformation in Reykjanes, in which each inflation period is caused by the intrusion of magmatic fluids into an aquifer at approximately 4 km depth. The aquifer resembles the approximate shape and location of the geothermal field outlined in Figure 1.…”
Section: Correlation With Deformation and Associated Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study focuses on the Reykjanes peninsula (SW Iceland), where an intense unrest period took place in 2020 in the area of the Svartsengi geothermal field (Figure 1). The unrest period consisted of three episodes of crustal inflation between January and August of 2020 and preceded a series of eruptions (Flovenz et al, 2022). Each inflation episode was followed by crustal deflation and associated with a large number of small to moderate earthquakes (M<4.8).…”
Section: Introductionmentioning
confidence: 99%